Diaphragm and lithium ion battery

By designing mesh or special-shaped coatings on the lithium-ion battery separator, providing electrolyte infiltration and gas discharge channels, the problem of slowing Li+ transmission speed and uneven SEI film caused by the increase in the separator thickness is solved, and the charging and discharging efficiency of the battery is improved and cycle performance.

CN119181930APending Publication Date: 2024-12-24TIANJIN JUYUAN NEW ENERGY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411243945.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

During use, lithium-ion batteries are slowed down due to the increase in the thickness of the separator, the charge and discharge efficiency are reduced, and the rate performance and cycle performance are deteriorated. At the same time, uneven SEI films are easily formed during the transformation process, resulting in the risk of failure.

Method used

Design a membrane, including a coating layer on the surface of the base film, the coating layer is a mesh or a special-shaped coating, with regular or irregular pores or channels, providing an electrolyte infiltration channel and a side reaction gas discharge channel, optimizing electrolysis Liquid infiltration uniformity and SEI film formation.

Benefits of technology

The electrolyte infiltration time is shortened, the charge and discharge efficiency and cycling performance are improved, the uniformity and stability of the SEI film are enhanced, and the thickness and energy density loss of the battery are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181930A_ABST
    Figure CN119181930A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly relates to a diaphragm and a lithium ion battery. The diaphragm comprises a diaphragm base membrane and a coating layer arranged on the surface of the diaphragm base membrane; the coating layer is a porous coating layer; the pore coating layer comprises a reticulate pattern coating layer or a special-shaped coating layer; the reticulate pattern coating comprises a parallel reticulate pattern coating layer or a crossed reticulate pattern coating layer; the special-shaped coating comprises a special-shaped coating line; regular or irregular pores or channels are formed between the reticulate pattern coating lines and the special-shaped coating lines. The pores or channels provide electrolyte infiltration channels and side reaction gas discharge channels, so that the infiltration time after liquid injection can be shortened, and meanwhile, the uniformity, compactness and stability of a surface SE I film are improved by optimizing the electrolyte infiltration uniformity and timely discharging gas generated by side reaction in the formation process; therefore, the charge-discharge efficiency and the cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and in particular relates to a diaphragm and a lithium-ion battery. Background Art

[0002] In recent years, the lithium-ion battery industry has experienced rapid growth with the widespread application of lithium-ion batteries. Lithium-ion batteries primarily consist of positive and negative electrode materials, electrolytes, and separators. As a key component of lithium-ion batteries, the separator plays an important role in maintaining battery safety and improving performance. It primarily isolates the positive and negative electrodes, preventing direct contact and short circuits, while allowing electrolyte ions to pass through, playing a crucial role in the electrical performance and safety of lithium-ion batteries.

[0003] The reaction mechanism of lithium-ion batteries is Li + The reversible embedding and unembedding process between the positive and negative electrode materials through the separator. Lithium-ion battery separators have good insulation, high corrosion resistance, high heat resistance and stability, high mechanical strength, and sufficient pore size and porosity to allow lithium ions to pass through while preventing other substances from passing through. However, in actual use, in order to ensure the safety performance of the battery, it often causes the loss of lithium-ion battery electrical performance. For example, in order to reduce the thermal shrinkage of the separator in high-capacity batteries, the thickness of the separator is increased, and ceramic is coated on one or both sides. This will result in Li ion battery failure during the charge and discharge process. + Slower transmission speeds reduce charge and discharge efficiency, worsen rate and cycle performance, and increase battery thickness, leading to a loss of energy density. Furthermore, lithium-ion batteries generate gas during the formation of the SEI film, making it difficult to expel bubbles from the negative electrode surface and unevenly forming the SEI film, leading to the risk of failure during cycling. Summary of the Invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a diaphragm and a lithium ion battery.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A diaphragm, comprising a diaphragm base film and a coating layer arranged on the surface of the diaphragm base film;

[0007] The coating layer includes a textured coating or a profiled coating;

[0008] The textured coating layer includes a parallel textured coating layer or a cross textured coating layer; the parallel textured coating layer includes a plurality of parallel textured coating lines; the cross textured coating layer includes a plurality of cross textured coating lines;

[0009] The profiled coating includes a profiled coating line;

[0010] Regular or irregular pores or channels are formed between the textured coating lines and the special-shaped coating lines.

[0011] The thickness of the coating layer on one side is t, 0.1um≤t≤20um, preferably 2μm.

[0012] The width of the textured coating lines and the profiled coating lines is independently m; 0.1 mm ≤ m ≤ 20 mm. The distance between adjacent parallel textured lines in the parallel textured coating layer is d1, 0.1 mm ≤ d1 ≤ 20 mm. The coating angle is a1, 0° ≤ a1 ≤ 180°. Preferably, 30° ≤ a1 ≤ 60°; m1 = 1 mm; d1 = 2 mm.

[0013] The crossing angle of the textured coating lines in the cross-textured coating layer is a2; 0°≤a2≤180°, regular pores are formed between the crossed textured coating lines; the pore length is d2, 0.1mm≤d2≤20mm.

[0014] Preferably, 30°≤a2≤60°; m2=1mm; d2=2mm.

[0015] The gap formed between the special-shaped coating lines is a triangle or a polygon.

[0016] As one form thereof, the gap formed between the special-shaped coating lines is a "convex" twelve-sided structure; the distance between the head and tail of the "convex" structure is d3, 0.1mm≤d3≤20mm.

[0017] Preferably, d3=6 mm.

[0018] A dot coating layer is provided on one side of the coating layer close to the edge of the diaphragm; the width of the dot coating layer is c, c≥(bs) / 2; wherein b is the width of the diaphragm, and s is the width of the positive electrode sheet.

[0019] Preferably, c=1.5 mm.

[0020] The dot coating layer is a high-temperature resistant, high-strength diaphragm coating layer; preferably, the dot coating layer is an aramid coating; preferably, the thickness of the dot coating layer is 0.1-5μm; preferably 1μm; the present invention also includes a lithium-ion battery, including the diaphragm; the positive and negative electrodes and the diaphragm are assembled into lithium-ion batteries of different structures by winding or laminating.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] In the solution of the present application, a functional coating layer is coated on the diaphragm, and at least regular or irregular pores or channels are provided in the coating layer; the pores or channels provide electrolyte infiltration channels and side reaction gas discharge channels, which can not only shorten the infiltration time after liquid injection, but also improve the uniformity, density and stability of the surface SE I film by optimizing the electrolyte infiltration uniformity and timely discharge of side reaction generated gases during the formation process, thereby improving the battery charge and discharge efficiency and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the structure of the diaphragm of Example 1;

[0024] Figure 2 Schematic diagram of the structure of the diaphragm of Example 2;

[0025] Figure 3 Schematic diagram of the structure of the diaphragm of Example 3;

[0026] Figure 4 Schematic diagram of the structure of the diaphragm of Example 4. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings and the best embodiments.

[0028] A diaphragm, comprising a diaphragm base film 001 and a coating layer 002 arranged on the surface of the diaphragm base film;

[0029] The coating layer includes a textured coating or a profiled coating;

[0030] The textured coating layer includes a parallel textured coating layer or a cross textured coating layer; the parallel textured coating layer includes a plurality of parallel textured coating lines; the cross textured coating layer includes a plurality of cross textured coating lines;

[0031] The profiled coating includes a profiled coating line;

[0032] Regular or irregular pores or channels are formed between the textured coating lines and the special-shaped coating lines.

[0033] The thickness of the coating layer on one side is t, 0.1um≤t≤20um, specifically 0.1μm, 4μm, 10μm, etc., preferably 2μm.

[0034] The width of the textured coating line and the profiled coating line is independently m; 0.1mm≤m≤20mm, specifically 0.1mm, 4mm, 10mm, etc., preferably 1mm.

[0035] The distance between adjacent parallel mesh lines in the parallel textured coating layer is d1, 0.1 mm ≤ d1 ≤ 20 mm; the coating angle is a1, 0° ≤ a1 ≤ 180°. Preferably, 30° ≤ a1 ≤ 60°; m1 = 1 mm; and d1 = 2 mm.

[0036] The crossing angle of the textured coating lines in the cross-textured coating layer is a2; 0°≤a2≤180°, regular pores are formed between the crossed textured coating lines; the pore length is d2, 0.1mm≤d2≤20mm.

[0037] Preferably, 30°≤a2≤60°; d2=2mm.

[0038] The gap formed between the special-shaped coating lines is a triangle or a polygon.

[0039] As one form thereof, the gap formed between the special-shaped coating lines is a "convex" twelve-sided structure; the distance between the head and tail of the "convex" structure is d3, 0.1mm≤d3≤20mm.

[0040] Preferably, d3=6 mm.

[0041] A dot coating layer is provided on one side of the coating layer close to the edge of the diaphragm; the width of the dot coating layer is c, c≥(bs) / 2; wherein b is the width of the diaphragm, and s is the width of the positive electrode sheet.

[0042] Preferably, c=1.5 mm.

[0043] The dot-shaped coating layer is a high-temperature resistant, high-strength diaphragm coating layer; preferably, the dot-shaped coating layer is an aramid coating; preferably, the thickness of the dot-shaped coating layer is 0.1-5 μm; preferably, it is 1 μm.

[0044] The following is a description of specific embodiments. Figure 1 A form of a diaphragm of Examples 1 and 2 is shown, wherein the coating layer is a textured coating in a porous coating layer; the coating angle is a1; the distance between adjacent parallel textured lines is d1, and the textured coating line width is m; a1=30°, m=1mm, d1=2mm (Example 1), a1=30°, m=1mm; d1=6mm (Example 2).

[0045] Figure 2 A form of a diaphragm of Example 3 is shown, wherein the coating layer is a cross-texture coating in a porous coating layer; the crossing angle of the textured coating lines in the cross-texture coating layer is a2; a2=45°; regular pores are formed between the cross-textures; the pore length is d2; d2=2mm.

[0046] Figure 3 A form of a diaphragm of Example 4 is shown, wherein the coating layer is a form of a special-shaped coating in a porous coating layer; the gap formed between the special-shaped coating lines is a "convex" twelve-sided structure; the distance between the head and tail of the "convex" structure is d3, d3 = 6mm.

[0047] Figure 4 A diaphragm form of Example 5 is shown, in which a dot coating layer is provided on one side of the coating layer close to the edge of the diaphragm; the width of the dot coating layer is c, c≥(bs) / 2; wherein b is the width of the diaphragm, s is the width of the positive electrode sheet, and as one form thereof, c=1.5 mm.

[0048] The material of the diaphragm base film is one or a combination of PP, PE, PP, PE, PI or PEEK; the coating method is one of gravure roller coating, dip coating, narrow coating or spray coating;

[0049] The coating layer includes a binder and an insulating material; the binder is a mixture of one or more of polyvinylidene fluoride, polyethylene oxide, polyether, polymethyl methacrylate, polyacrylonitrile, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyvinylidene fluoride and polyethylene glycol;

[0050] The insulating material is one or more of Al2O3, AlOOH, γ-AlOOH, SiO2, TiO2, ZrO2, SnO2, MgO, ZnO, CaO, CeO2, Y2O3, BaTiO3, SrTiO3, and LAGP. In this application, a mixture of MgO and Al2O3 in a mass ratio of 1:1 is used as the insulating material, and PVDF is used as the binder as a preferred example.

[0051] The diaphragm materials of Examples 1-4 were prepared as follows: a mixture of MgO and Al2O3 was added to an aqueous solution containing PVDF (7.5% by weight) and stirred to obtain a uniform coating slurry. The slurry was then coated on the surface of a PE base film (made by Zhuhai Enjie, thickness: 5 μm) using a coating machine by roller coating, and then vacuum dried at 60°C for 12 h to obtain a diaphragm provided with a coating layer.

[0052] The diaphragm material of Example 5 is prepared in the following manner: first, the overall textured coating part is prepared in accordance with the diaphragm preparation method of Example 3, and then a layer of aramid coating is applied on the top as a dot coating layer. The coating of the aramid coating is prepared in the following manner: the oily solvent NMP and PMIA are heated and stirred in a mass ratio of 8:2 (80°C, 30min) and then coated on the above-mentioned textured ceramic coating. The coating width is c = 1.5mm and the thickness is 1um, and a diaphragm with a 1.5mm high-temperature resistant, high-strength coating layer on the top is obtained.

[0053] The positive electrode sheet was prepared by mixing the positive electrode active material LiCoO2, the conductive agent CNT, and the binder PVDF in a mass ratio of 97.5:1.5:1, adding the solvent NMP and stirring in a vacuum mixer to obtain a uniform positive electrode active slurry; the positive electrode active slurry was coated on the current collector Al foil and dried, rolled, and sheared to obtain the positive electrode sheet.

[0054] The negative electrode sheet was prepared by mixing the negative electrode active material graphite, the conductive agent Super P, the thickener CMC, and the binder SBR in a mass ratio of 97.5:0.5:0.9:1.1, adding the solvent deionized water and stirring in a vacuum mixer to obtain a uniform negative electrode active slurry; the negative electrode active slurry was coated on the current collector Cu foil and dried, rolled, and sheared to obtain the negative electrode sheet.

[0055] The prefabricated positive electrode sheet, negative electrode sheet and the separator obtained in Examples 1-5 were respectively made into lithium-ion battery cells in a winding manner, and lithium-ion batteries were obtained after aluminum-plastic shell packaging, drying, liquid injection, standing, fixture formation, and capacity division.

[0056] Table 1 shows the preparation parameters of the separators of different examples, with a fully coated separator as a comparative example.

[0057] Table 1

[0058]

[0059] The liquid retention, initial voltage and electrical performance of the lithium-ion batteries assembled with the diaphragms described in Examples 1 to 5 and the comparative example were tested as follows:

[0060] Liquid retention and initial voltage test: Batteries filled with the same electrolyte were placed at 40°C for 24 hours, 36 hours, and 48 hours, and the initial voltage of the battery cells was recorded at different times for different embodiments. Generally, the initial voltage of an unformed rechargeable battery reflects the electrolyte infiltration status, and a stable voltage indicates complete electrolyte infiltration.

[0061] Capacity test: At 25°C, the battery was charged at a constant current of 0.2 C min to 4.45 V, and then charged at a constant voltage of 4.45 V until the current dropped to 0.05 C min to obtain the charge capacity. After the battery rested for 10 minutes, it was discharged at a constant current of 0.2 C min to 3.0 V to obtain the discharge capacity.

[0062] K value: At 25°C, the battery was charged at a constant current of 0.2 C min to 3.9 V, and then charged at a constant voltage of 3.9 V until the current dropped to 0.05 C min. After standing for 24 ± 12 h, the battery voltage was tested using an electrochemical workstation to obtain the battery voltage OCV1. After further standing for T (72 ± 12 h), the voltage was tested using an electrochemical workstation to obtain OCV2. K value = (OCV1 - OCV2) / T

[0063] Cycling test: At 25°C, the battery was charged at a constant current of 1 C / min to 4.45V. Then, it was charged at a constant voltage of 4.45V until the current dropped to 0.05 C / min, and the charge capacity was obtained. After the battery rested for 10 minutes, it was discharged at a constant current of 0.5 C / min to 3.0V. These steps were repeated for the battery, and the number of cycles required to achieve a capacity ≥ 80% was recorded.

[0064] Hot box test: At 25°C, the battery is charged at a constant current of 1C / min to 4.45V, and then charged at a constant voltage of 4.45V until the current drops to 0.05C / min. The battery is placed in a room temperature oven and the temperature is increased at 5°C / min until the oven temperature reaches 130°C and maintained for 0.5h. The maximum temperature of the battery surface is recorded.

[0065] Table 2 shows the test results of Examples 1 to 5 and the comparative example.

[0066] Table 2

[0067]

[0068] The above test results reflect that: by comparing Examples 1 to 5 and the comparative example, it can be seen that when the liquid retention capacity is the same, the static time required after the diaphragm coating is coated with diagonal, reticulated, and combined coatings is shorter, which can be shortened by more than 12 hours. Moreover, under the same static time, the capacity of the diaphragm of this invention is higher and the number of cycle capacity is more, and the K value of the battery is not affected. This proves that the diaphragm of this invention can not only shorten the infiltration time after liquid injection, but also improve the uniformity, density and stability of the surface SEI film by optimizing the uniformity of electrolyte infiltration and timely discharge of side reaction gases during the formation process, thereby improving the battery cycle performance. The insulating layer coated on the diaphragm can also ensure the safety and electrical performance of the lithium-ion battery by changing the coating material.

[0069] It should be noted that the ceramic insulating layer or other functional coating on the diaphragm can be coated on one side or on both sides. The coating material can be optimized according to the battery performance. Figure 4In the battery, the contact area between the diaphragm and the positive and negative electrodes can be coated with functional materials such as ceramic glue to ensure the electrochemical performance of the battery. The non-contact top position can be coated with insulating materials with better thermal stability or higher strength to reduce the risk of thermal failure of the battery.

[0070] In summary, the solution of the present application is to coat a functional coating layer on the diaphragm, and at least regular or irregular pores or channels are provided in the coating layer; the pores or channels provide electrolyte infiltration channels and side reaction gas discharge channels, which can not only shorten the infiltration time after injection, but also improve the uniformity, density and stability of the surface SE I film by optimizing the electrolyte infiltration uniformity and timely discharge of the side reaction generated gas during the formation process, thereby improving the battery charge and discharge efficiency and cycle performance.

[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A diaphragm, characterized in that: It includes a diaphragm base film and a coating layer arranged on the surface of the diaphragm base film; The coating layer includes a textured coating or a profiled coating; The textured coating comprises a parallel textured coating layer or a cross textured coating layer; the parallel textured coating layer comprises a plurality of parallel textured coating lines; the cross textured coating layer comprises a plurality of cross textured coating lines; The profiled coating includes a profiled coating line; Regular or irregular pores or channels are formed between the textured coating lines and the special-shaped coating lines.

2. The diaphragm according to claim 1, characterized in that The thickness of the coating layer on one side is t, 0.1um≤t≤20um.

3. The diaphragm according to claim 1, characterized in that The width of the textured coating line and the profiled coating line are independently m; 0.1mm≤m≤20mm.

4. The diaphragm according to claim 1, characterized in that The distance between adjacent parallel mesh lines in the parallel mesh coating layer is d1, 0.1mm≤d1≤20mm; the coating angle is a1, 0°≤a1≤180°.

5. The diaphragm according to claim 1, characterized in that The crossing angle of the textured coating lines in the cross-textured coating layer is a2; 0°≤a2≤180°, regular pores are formed between the crossed textured coating lines; the pore length is d2, 0.1mm≤d2≤20mm.

6. The diaphragm according to claim 1, characterized in that The gap formed between the special-shaped coating lines is a triangle or a polygon.

7. The diaphragm according to claim 6, characterized in that The gap formed between the special-shaped coating lines is a "convex" twelve-sided structure; the distance between the head and the tail of the "convex" structure is d3, 0.1mm≤d3≤20mm.

8. The diaphragm according to claim 1, characterized in that A dot coating layer is provided on one side of the coating layer close to the edge of the diaphragm; the width of the dot coating layer is c, c≥(bs) / 2; wherein b is the width of the diaphragm, and s is the width of the positive electrode sheet.

9. The diaphragm according to claim 8, characterized in that The dot-shaped coating layer is a high-temperature resistant, high-strength diaphragm coating layer; preferably, the dot-shaped coating layer is an aramid coating; preferably, the thickness of the dot-shaped coating layer is 0.1-5 μm; preferably, 1 μm.

10. A lithium ion battery, characterized in that: A diaphragm comprising any one of claims 1 to 8; Preferably, the material of the diaphragm base film is one or a combination of PP, PE, PP, PE, PI or PEEK; the coating method is one of gravure roller coating, dip coating, narrow coating or spray coating; The coating layer includes a binder and an insulating material; the binder is a mixture of one or more of polyvinylidene fluoride, polyethylene oxide, polyether, polymethyl methacrylate, polyacrylonitrile, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyvinylidene fluoride and polyethylene glycol; The insulating material is one or a mixture of multiple of Al2O3, AlOOH, γ-AlOOH, SiO2, TiO2, ZrO2, SnO2, MgO, ZnO, CaO, CeO2, Y2O3, BaTiO3, SrTiO3, and LAGP.